"A Nation-wide Chain within 60 Days": Radio Network Failure in Early American Broadcasting. Issue 1 (2nd January 2016) - Socolow, Michael J.
Abstract : Numerous failed attempts to develop new national commercial broadcasting companies occurred during American network radio's first decade. These unsuccessful endeavors raise important questions concerning barriers to entry faced by entrepreneurs seeking access to the nation's airwaves. This article examines three such cases in order to develop a more detailed understanding of alternatives, contingency, and historical inevitability in broadcasting history. It reveals the complex intertwining of multiple variables required for success. Because the examples involve one of the United States' most popular radio entertainers (Ed Wynn), one of the nation's wealthiest citizens (Samuel Insull), and one of the industry's pioneering executives (George McClelland), they are not representative. These are exceptional cases, yet they all failed despite possessing significant advantages unavailable to others.